Religious People's Perception of the Kapuhunan Myth - Nadia Hafifa Maulaya; Agus Machfud Fauzi (Asketik)
Culture is an essential element of social life that influences people's norms and behaviors. Mythologies, especially those with religious and belief dimensions, play a key role in shaping human values and morals. Religion, tradition and myth become the moral framework that protects life in the social order. The Kapuhunan myth in Kalimantan reflects a shift in people's perception of bad luck, especially in Pangkalan Bun City. This research uses a qualitative approach with an interview method to understand how this myth influences the perception of religious communities. This myth is regarded as a symbol of supernatural power that brings disaster, believed by both natives and migrants, shaping the view of food as a determinant of bad luck. From a religious perspective, there is a moral dilemma between conventional beliefs and religious teachings. In Max Weber's theory of social action, instrumental rational, value, affective and traditional actions are reflected in the respect for the Kapuhunan myth. The analysis shows that this myth influences various types of social actions, shapes the behavior of people in Pangkalan Bun City, and raises a dilemma between traditional beliefs and religious teachings.